1908. Development of an Electronic Health Record Generated Alert for Prophylaxis Against Pneumocystis Jirovecii Pneumonia in the Setting of High-Dose Steroids. (26th November 2018) - Goyal, Noopur; Gaskill, Eric; Sanders, Stephanie; Graves, Kencee; Benefield, Russell; ElHalta, David; Link, Nicholas C; Cariello, Paloma
Abstract: Background: Pneumocystis jirovecii pneumonia (PJP) is an opportunistic infection associated with high dose steroid use in non-HIV patients. Many patients on high dose steroids (>20 mg prednisone equivalents for 28 days or longer), developed PJP within a month of steroid use. This study aims to develop an electronic alert for providers to consider PJP prophylaxis for patients discharged on high-dose steroids. Methods: Cases were obtained from the University of Utah Enterprise Data Warehouse between October 2014 and September 2017. A retrospective, manual chart review evaluated adults 18 years of age or older, with an inpatient PJP diagnosis made via direct fluorescent antibody or PCR. Patients with PJP due to HIV were excluded. Steroid dose and duration one month prior to diagnosis of PJP were evaluated. After retrospective analysis, via a multidisciplinary team, a best practice advisory (BPA) alert was created to flag providers to consider PJP prophylaxis at discharge, with consideration of creatinine levels and allergy profile to guide drug choices. The alert was trailed in a silent mode from January to April 2018 without provider notification so it could be modified to prevent inappropriate firing. The alert was approved for live use by the Clinical Decision Support Committee and is now active in the University of Utah Epic system as of April 10, 2018. Results: In retrospective analysis, of 94 non-HIV patients diagnosed with PJP, 31/94 (33%) cases were in the setting of high dose steroids. 7/31 (23%) cases were exclusively with high dose steroids, while 24/31 (77%) cases were in combination with chemotherapy or other immune modulating agents. Data from the silent BPA from February to April 2018 demonstrated 23 cases triggered the alert, all of which were determined to be appropriate by chart review. Since live use, the BPA has fired 15 times, of which 14 cases met criteria for prophylaxis and 4/14 (29%) resulted in prophylaxis on discharge. Conclusion: Chart review identified high dose steroids as a target for a quality improvement intervention, which led to development of a BPA. Data indicates room for improvement on discharge with prophylaxis. Goals include reducing morbidity, mortality and cost associated with PJP, as well as educating providers regarding the need for prophylaxis. Disclosures: All authors: No reported disclosures.